Knowledge and Attitudes of the Population in Parakou Regarding Endemic Limbo- Conjunctivitis of the Tropics in 2022 - ALFA BIO ISSIFOU, Amadou; ABOUKI, CHAKIRATOU O.A.; AIGBE, Nestor; MONTEIRO, Salimatou; KODJO, Amèfa Agnès Bernice; LOKOSSI, André; ASSAVEDO, Codjo Rodrigue Abel; ALAMOU, SOULÉ; ODOULAMI-YEHOUESSI, LISETTE; SOUNOUVOU, IGNACE ADJOVIGNON (My University, 2023)
Abstract Introduction: Conjunctivitis is a worldwide public health problem and is particularly widespread in sub-Saharan Africa, especially the vernal kerato-conjunctivitis (VKC). Although it is not the main cause of functional visual impairment, especially in children. The aim of this study is to assess the knowledge and attitudes of the population of Parakou in Benin regarding VKC in 2022. Method: This was a descriptive cross-sectional survey conducted over one month in the district of Parakou in August 2022. Three-level cluster sampling was done and included participants aged 18 and over. Data were collected via individual interviews using a smartphone-based electronic questionnaire. Statistical analysis used Stata 15, including bivariate analysis and logistic regression for associations. Results: Of the 750 participants, 66% were female, with an average age of 29.5 years. Non-educated participants accounted for 54.93%, and 31.73% were craftsmen. Knowledge of the VKC was good in 16.80% of cases, while attitudes were favorable in 69.33%. Multivariate analysis showed that gender was associated with knowledge (higher risk for women). Attitudes were influenced by sex, marital status and level of education. Conclusion: Awareness of the VKC is low at Parakou in Republic of Benin, despite favorable attitudes. Women are at greater risk of poor knowledge. The final model proved adequate, underlining the importance of raising awareness of the VKC to improve people's knowledge and attitudes. Keywords: Conjunctivitis; Knowledge; Attitude
Keywords: Keywords: Conjunctivitis; Knowledge; Attitudes